Introduction: Political linkage and political space in the era of decolonization - Cheeseman, N (2006)
The continuing importance of Kenya's institutional colonial inheritance has been underestimated because the impact of decolonization on Kenya's formal political institutions has rarely been systematically addressed. Consequently, there is a pressing need to reevaluate the structure of government in the colonial and postcolonial periods in a manner that takes a critical perspective on the domestic relationship between government and opposition. In addition to introducing the papers that follow, this essay examines the factors that underpin the continued supremacy of the executive-administrative axis in the Kenya postcolony. It develops the twin concepts of political linkage and political space as tools to describe the political landscape of the colonial and postcolonial eras. Institutional factors, it is argued, must be central to any attempt to explain the longevity and eventual breakdown of KANU rule.